ASIC1a activation induces calcium-dependent apoptosis of BMSCs under conditions that mimic the acidic microenvironment of the degenerated intervertebral disc. Issue 11 (13th November 2019) - Cai, Feng; Hong, Xin; Tang, Xiang; Liu, Nai-Cheng; Wang, Feng; Zhu, Lei; Xie, Xin-Hui; Xie, Zhi-Yang; Wu, Xiao-Tao
Abstract: Purpose: In the degenerated intervertebral disc (IVD), matrix acidity challenges transplanted bone marrow mesenchymal stem cells (BMSCs). The Ca 2+ -permeable acid-sensing ion channel 1a (ASIC1a) is responsible for acidosis-mediated tissue injury. The aim of our study was to confirm whether ASIC1a activation induces BMSC apoptosis under conditions that mimic the acidic microenvironment of the degenerated IVD. Methods: ASIC1a expression in rat BMSCs was investigated by real time-PCR, Western blot (WB) and immunofluorescence. The proliferation and apoptosis of BMSCs under acidic conditions were analyzed by MTT and TUNEL assays. Ca 2+ -imaging was used to assess the acid-induced increase in the intracellular Ca 2+ concentration ([Ca 2+ ]i). The activation of calpain and calcineurin was analyzed using specific kits, and WB analysis was performed to detect apoptosis-related proteins. Ultrastructural changes in BMSCs were observed using transmission electron microscopy (TEM). Results: Acid exposure led to the activation of ASIC1a and increased BMSC apoptosis. The Ca 2+ imaging assay showed a significant increase in the [Ca 2+ ]i in response to a solution at pH 6.0. However, BMSC apoptosis and [Ca 2+ ]i elevation were alleviated in the presence of an ASIC1a inhibitor. Moreover, ASIC1a mediated the Ca 2+ influx-induced activation of calpain and calcineurin in BMSCs. WB analysis and TEM revealed mitochondrial apoptosis, which was inhibited by an ASIC1a inhibitor, in BMSCs under acidic conditions. Conclusions: The mimical acidic microenvironment of the degenerated IVD can induce BMSC apoptosis by activating Ca 2+ -permeable ASIC1a. An acid-induced elevation of [Ca 2+ ]i in BMSCs leads to the subsequent activation of calpain and calcineurin, further resulting in increased mitochondrial permeability and mitochondrial-mediated apoptosis.